2016
DOI: 10.1017/s0016756816001011
|View full text |Cite
|
Sign up to set email alerts
|

The Shackleton Range (East Antarctica): an alien block at the rim of Gondwana?

Abstract: The Shackleton Range is a truncated Pan-African Orogen situated at the Weddell Sea margin of East Antarctica. It almost exclusively consists of basement rocks exposed at an elevated, escarpment-bound palaeosurface and is covered locally by patchy remnants of Ordovician, Permian and, controversially, Jurassic terrestrial deposits. This inventory does not match the geological record of any other place in Antarctica. Here we reconstruct the Phanerozoic evolution of the Shackleton Range by means of a multi-discipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…This scenario implies that parts of the present‐day landscape of Thurston Island formed already in the Jurassic and thus >80 Myr prior to the mid‐Cretaceous landscape architecture of Marie Byrd Land. Between the Early Jurassic and Early Cretaceous, Thurston Island was characterized by heating, which we interpret as burial resulting from back‐arc basin development following widespread Early Jurassic volcanism. Basin development on Thurston Island shows striking similarities with the Mesozoic basins in the Shackleton Range (Krohne et al, ) and the Transantarctic Mountains (Lisker & Läufer, ). All these basins initiated by the Early Jurassic and thus indicate that Mesozoic intra‐Gondwana extension extended over larger areas than previously thought. All basement units in the Thurston Island area experienced cooling at ~135–125 Ma, corresponding with crustal thickening and rapid erosion of almost the complete Early Jurassic‐Early Cretaceous basin deposits due to basin inversion until ~95 Ma.…”
Section: Discussionmentioning
confidence: 93%
“…This scenario implies that parts of the present‐day landscape of Thurston Island formed already in the Jurassic and thus >80 Myr prior to the mid‐Cretaceous landscape architecture of Marie Byrd Land. Between the Early Jurassic and Early Cretaceous, Thurston Island was characterized by heating, which we interpret as burial resulting from back‐arc basin development following widespread Early Jurassic volcanism. Basin development on Thurston Island shows striking similarities with the Mesozoic basins in the Shackleton Range (Krohne et al, ) and the Transantarctic Mountains (Lisker & Läufer, ). All these basins initiated by the Early Jurassic and thus indicate that Mesozoic intra‐Gondwana extension extended over larger areas than previously thought. All basement units in the Thurston Island area experienced cooling at ~135–125 Ma, corresponding with crustal thickening and rapid erosion of almost the complete Early Jurassic‐Early Cretaceous basin deposits due to basin inversion until ~95 Ma.…”
Section: Discussionmentioning
confidence: 93%
“…Another option is that the observed asymmetry in the topography is the result of spatially variable erosion rather than spatially variable uplift. However, this is unlikely to be the case, since the tilt is observed in the mesa/plateau surfaces (Figure ), which have experienced negligible incision and cut different geological units [ Kerr and Hermichen , ; Sugden et al ., ; Krohne et al ., ]. The presence of surfaces that all tilt away from the region of unloading and have slopes that are not the same as geological dip slopes is strong evidence for flexural tilting [ Watts et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The timing and mechanism(s) responsible for the uplift of the Shackleton Range and Theron Mountains and the subsidence of the Recovery, Slessor, and Bailey troughs remain outstanding questions. Apatite fission track and (U‐Th)/He dating indicate multiple phases of denudation and burial of the Shackleton Range in the Mesozoic before final uplift and formation of the present landscape since EAIS inception at 34 Ma [ Krohne et al ., ]. Previous studies have suggested that the uplift of the mountain ranges and subsidence of the troughs are inherently coupled.…”
Section: Introductionmentioning
confidence: 99%
“…The second commenced in the Jurassic following emplacement of the Ferrar Large Igneous Province, the onset of rifting in the Weddell Sea, and the subsequent breakup of Gondwana and onset of seafloor spreading between Africa and East Antarctica (Jordan et al, 2017;Leinweber & Jokat, 2012). AFT data indicate that up to 4 km of post-Jurassic sediments were deposited in a "Mesozoic Victoria Basin" that extended from Coats Land to Victoria Land (Krohne et al, 2016;Lisker et al, 2014;Lisker & Läufer, 2013;Prenzel et al, 2018), although such rocks have not been directly observed in East Antarctica.…”
Section: Geology Of the Pensacola-pole Basinmentioning
confidence: 99%
“…Apatite fission track (AFT) and (U-Th)/He thermochronology data, alongside thermal history modeling, have been interpreted as reflecting two phases of burial of the basement along the East Antarctic margin from Victoria Land to Coats Land by sedimentary successions since the mid-Paleozoic (Krohne et al, 2016;Lisker et al, 2014;Lisker & Läufer, 2013;Prenzel et al, 2018). The first phase was associated with the deposition of Beacon Supergroup strata along the subduction-dominated Panthalassan margin of Gondwana in a series of basins referred to collectively as the Transantarctic Basin (Collinson et al, 1994).…”
Section: Geology Of the Pensacola-pole Basinmentioning
confidence: 99%